Comparative effects of plasma exchange and pyridostigmine on respiratory muscle strength and breathing pattern in patients with myasthenia gravis. Issue 10 (October 1995) - Goti, P; Spinelli, A; Marconi, G; Duranti, R; Gigliotti, F; Pizzi, A; Scano, G
Abstract : BACKGROUND–Pyridostigmine, an acetylcholinesterase antagonist, is useful in improving respiratory function in patients with myasthenia gravis. More recently, plasma exchange has been employed in myasthenia gravis because it acts presumably by removal of circulating antibodies against acetylcholine receptors. Surprisingly, comparative data on the effects of pyridostigmine and plasma exchange on lung volumes, respiratory muscle strength, and ventilatory control system in patients with myasthenia gravis are lacking. METHODS–Nine consecutive patients with grade IIb myasthenia gravis were studied under control conditions and after a therapeutic dose of pyridostigmine. In a second study the patients were re-evaluated a few days after a cycle of plasma exchange, before taking pyridostigmine. In each subject pulmonary volumes, inspiratory (MIP) and expiratory (MEP) muscle force, and respiratory muscle strength, calculated as average MIP and MEP as percentages of their predicted values, were measured. The ventilatory control system was evaluated in terms of volume (tidal volume, VT) and time (inspiratory time, TI, and total time, TTOT) components of the respiratory cycle. Mean inspiratory flow (VT/TI)–that is, the "driving"–and TI/TTOT–that is, the "timing"–components of ventilation were also measured. RESULTS–In each patient treatment relieved weakness and tiredness, and dyspnoea grade was reduced with plasma exchange. Following treatment, vital capacity (VC) increased on average by 9.7% with pyridostigmine and by 14% with plasma exchange, and MIP increased by 18% and 26%, respectively. In addition, with plasma exchange but not with pyridostigmine forced expiratory volume in one second (FEV1) increased by 16% and MEP increased by 24.5%, while functional residual capacity (FRC) decreased a little (6.8%). The change in respiratory muscle strength was related to change in VC (r2 = 0.48). With plasma exchange, VT increased by 18.6% and VT/TI increased by 13.5%, while neither TI nor TI/TTOT changed. CONCLUSIONS–Plasma exchange can be used in patients with myasthenia gravis when symptoms are not adequately controlled by anticholinesterase agents. Plasma exchange increases respiratory muscle force and tidal volume due to changes in "driving" but not "timing" of the respiratory cycle.